THE USE OF TEACHERâ€™S CODE SWITCHING IN ENGLISH TEACHING - Eko Author (Journal of Applied Linguistics (ALTICS), 2019)
This research is to describe code switching that teacher used in teaching process. The researcher wants to analysis the type and the function of using code switching by teacher because English is not compulsory subject in elementary school and English is still unfamiliar for Indonesian students. The subject was English teacher who teaches in seventh grade at SMPN 1 Parungponteng, Tasikmalaya. Based on the research, the teacher practiced code switching in order to help the students in delivering materials. In the process of code switching, the teacher practiced Bahasa Indonesia, Sundanese and English. The aims of this research were to classify the types of code switching and functions of code switching. It was descriptive qualitative research designs of which instrument are both observation and interview. The findings from the data analysis indicated that the types of code switching were found in three types: inter-sentential switching, intra-sentential switching, tag switching. The functions of code switching used by the teacher were found three functions: message reiteration, message qualification and interjection. Furthermore, the type reason of using code switching by teacher based on interview was repetition used for clarification because the teacher wants students understand what teacher has explained.Â Keyword: code switching, sociolinguistics, bilingualism, English as a foreign language, EFL teaching.